The Washington Redskins : when public perception challenges a brand - Ludwig, Carson, (SAGE Business. Cases., 2020)
The Washington Redskins professional football team face a new social climate with the sudden rise of power and influence of the Black Lives Matter Movement. The team, its owners, sponsors and fans confront a momentous shift in American tolerance for racially charged brands following the death George Floyd in 2020. Sponsorship arrangements, logotypes, even the team's name are under fire.